Air-breathing fishes : - Graham., Jeffrey B. (Academic Press, 1997)
Air Breathing Fishes: Evolution, Diversity, and Adaptation is unique in its coverage of the evolution of air-breathing, incongruously because it focuses exclusively on fish. This important and fascinating book, containing nine chapters that present the life history, ecology, and physiology of many air-breathing fishes, provides an exceptional overview of air-breathing biology.